Ask Question
12 December, 06:11

Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth. - 2y2 + 6y = - 2

+2
Answers (1)
  1. 12 December, 06:34
    0
    -2y^2 + 6y + 2 = 0

    a = - 2, b = 6, c = 2

    x = ( - b + - sqrt (b^2-4ac)) / (2a)

    x = (-6+-sqrt (36-4*-2*2)) / - 4

    x = (-6+-sqrt (36+16)) / - 4

    x = (-6+-sqrt (52)) / - 4

    x = (-6 + - 2sqrt13) / - 4

    x = (3 + - sqrt13) / 2
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth. - 2y2 + 6y = - 2 ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers